2003
DOI: 10.1007/s00120-003-0401-9
|View full text |Cite
|
Sign up to set email alerts
|

V.�-cava-superior-Syndrom mit beidseitiger Jugularis- und Subklaviavenenthrombose

Abstract: At present thrombosis of the superior vena cava is an uncommon event that is now more frequently associated with diagnostic or therapeutic catheterization. If an apparent spontaneous thrombosis occurs, malignancy should be considered in the differential diagnosis. One case of clinically symptomatic thrombosis of the internal jugular, subclavian, and superior vena cava is presented. We detected an asymptomatic left renal cell carcinoma in a 54-year-old patient and nephrectomy was performed. Increased blood coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…In another report, a fatal outcome of pulmonary tumor thrombotic microangiopathy based on a papillary RCC was identified, in which tumorous microemboli formed in the pulmonary arterioles and subsequently lead to right heart failure [ 11 ]. Venous thrombosis in central retinal veins or the upper caval vein are further manifestations of PNS, probably aggravated by elevated levels of antiphospholipid and anticardiolipin antibodies [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another report, a fatal outcome of pulmonary tumor thrombotic microangiopathy based on a papillary RCC was identified, in which tumorous microemboli formed in the pulmonary arterioles and subsequently lead to right heart failure [ 11 ]. Venous thrombosis in central retinal veins or the upper caval vein are further manifestations of PNS, probably aggravated by elevated levels of antiphospholipid and anticardiolipin antibodies [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Santra et al reported paraneoplastic thrombus formation in SVC due to lung cancer. 5 Moreover, paraneoplastic causes of SVC syndrome due to thrombosis have been reported in association with renal cell carcinoma, 6 ovarian cancer 7 and Richter syndrome. 8 Obstruction of the SVC can also be due to intraluminal metastasis without thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosierungen der Vena jugularis interna waren in der präantibiotischen Zeit eine häufige Folge von entzündlichen Prozessen im Kopf-Hals-Bereich. Deutlich häufiger sind Thrombosierungen heute durch obere Einflussstauungen aufgrund neoplastischer Erkrankungen [16,17].…”
Section: Der Interessante Fallunclassified